MENGENALI KONTEKS AJARAN SOSIAL GEREJA KATOLIK ABAD XIX - Antonius Eddy Kristiyanto (Jurnal Orientasi Baru, 2012)
This article presents contextual arguments on the social problems addressed by the Catholic Church. The thought was developed in the 19th century with its industrialization that caused an enormous social as well as technological change, and that aimed a great social welfare. Unfortunately, industrialization was not identical with merely a social progress. Ideology such as liberalism or communism was conflictive and socially problematic. The victims have been the workers with their family amid the weakening of system of education, healthcare, morality and sense of faith. Involvement and intervention of the nation was supported by thinkers such as philosophers, experts in economy and politic as well as theologians and practitioners. Catholic Church with its option for the poor has based her vision on the fundamental commitment to human dignity, sacredness of life as well as the social nature of human being. Rerum Novarum, the encyclical letter of pope Leo XIII, presented a very significant insights concerning the world of workers, of policy makers, factory owners and people from human rights watch.